Portuguese digital cities and regions: an evaluation - Maria Jo\~ao Sim\~oes; Domingos Santos (European Regional Science Association (ERSA), 2012)
The purpose of this article is to contribute for the debate about the construction of governance spaces which guarantee the continuity of the regional development public policies, thus articulating actors and optimizing strategic projects in order to improve regional competitiveness ans sustainability. The call by European Union policymakers for wider and more direct involvement in improving European governance is coupled with the increased usage of new information and communications technologies (ICTs) by public administrations across the EU. Portugal has been strategically involved in a catching-up process with high investments in the areas of innovation and ICT infrastructures. This paper is based on the field work and on the results obtained by a research project that analyzed the Portuguese Digital Cities and Regions Program on a multi-dimensional way, covering mainly the areas of accessibility, e-government and territorial development. We argue that the recent revival of interest of the "digital" has been constructed around a rather narrow set of empirical and theoretical issues concerning mainly to technological innovation, neglecting other strategic political areas, such as the policies of governance and state re-territorialization, the concept of innovation and social innovation, the role of democracy and citizenship and tensions around social reproduction and sustainability across the digital cities and regions. The evidence provided by this research work shows that investments in ICT infrastructures, although very necessary, haven't been sufficient to create a sustainable knowledge-based living and working environment in Portugal. Most initiatives under the Digital Cities and Regions Program have been leading to interventions very much focused on infra-structure and undervaluing intangibles. Regional and city managers' and planners' attention could – indeed should – shift towards the `softer' but critical issues of filling the knowledge, expertise and organizational gaps. This requires a continuous public effort, but also a better understanding of the effectiveness of the mix of public support mechanisms and private incentives for the development of digital territories. These questions will be analyzed and discussed in the light of the Portuguese experience and some final considerations will be outlined concerning the content and the format that public policies should carry out in order to better promote territorial innovation policies. : digital city, digital region, e-government, governance innovation, territorial innovation policies.
Keywords: H76; O33; O38; R11; R58; 330